2011
DOI: 10.1111/j.1528-1167.2010.02930.x
|View full text |Cite
|
Sign up to set email alerts
|

Localized overexpression of FGF-2 and BDNF in hippocampus reduces mossy fiber sprouting and spontaneous seizures up to 4 weeks after pilocarpine-induced status epilepticus

Abstract: SUMMARYPurpose: We have recently reported that viral vectormediated supplementation of fibroblast growth factor-2 (FGF-2) and brain-derived neurotrophic factor (BDNF) in a lesioned, epileptogenic rat hippocampus limits neuronal damage, favors neurogenesis, and reduces spontaneous recurrent seizures. To test if this treatment can also prevent hippocampal circuit reorganization, we examined here its effect on mossy fiber sprouting, the best studied form of axonal plasticity in epilepsy. Methods: A herpes-based v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 32 publications
1
42
0
Order By: Relevance
“…However, early studies demonstrated that the increase in BDNF expression caused by seizure agents such as kainate did not further activate the full-length TrkB receptor and were not neuroprotective (Rudge et al 1995(Rudge et al , 1998. Recently, however, the role of the acute effects of BDNF expression and receptor activation in seizure models remains controversial (Binder et al 2001;Bovolenta et al 2010;Heinrich et al 2011;Paradiso et al 2011;Reibel et al 2001). Overall, our results suggest that increased mature BDNF protein levels in neurons correlate with the activation of downstream signaling events possibly via activation of TrkB.…”
Section: Discussionmentioning
confidence: 46%
“…However, early studies demonstrated that the increase in BDNF expression caused by seizure agents such as kainate did not further activate the full-length TrkB receptor and were not neuroprotective (Rudge et al 1995(Rudge et al , 1998. Recently, however, the role of the acute effects of BDNF expression and receptor activation in seizure models remains controversial (Binder et al 2001;Bovolenta et al 2010;Heinrich et al 2011;Paradiso et al 2011;Reibel et al 2001). Overall, our results suggest that increased mature BDNF protein levels in neurons correlate with the activation of downstream signaling events possibly via activation of TrkB.…”
Section: Discussionmentioning
confidence: 46%
“…Apart from having neuroprotective function and the ability for enhancing NSC proliferation and neurogenesis, these factors can also improve cognitive and mood function [4953]. Additionally, GDNF can suppress seizures [54], and BDNF and FGF-2 can reduce epileptogenesis and hyperexcitability that ensue after hippocampal injury [55]. Second, NSC grafting added significant numbers of GABA-ergic neurons into the injured hippocampus.…”
Section: Introductionmentioning
confidence: 99%
“…Administration of neurotrophic factors is r e l e v a n t a s m a n y f a c t o r s t h a t p r o m o t e neurogenesis (e.g: BDNF, FGF-2, IGF-1) are reduced in chronic epilepsy . Supporting this, a range of studies have demonstrated that administration of neurotrophic factors to both the normal and injured adult rodent brain can enhance hippocampal neurogenesis (Lichtenwalner, et al, 2001, Yoshimura, et al, 2001, Scharfman, et al, 2005, Rai, et al, 2007, Paradiso, et al, 2009, Paradiso, et al, 2011. Performing physical exercise and environmental enrichment have also been shown to enhance hippocampal neurogenesis, potentially through increased expression of a range of mitogenic factors such as BDNF, FGF2, NGF, IGF-1 and VEGF as well as phosphorylation of cAMP-response binding protein (CREB) (Nithianantharajah, et al, 2006, Van Praag, 2008, Llorens-Martín, et al, 2009, Lafenetre, et al, 2011 and may provide an appealing noninvasive therapeutic approach for the treatment of chronic TLE (Dhanushkodi, et al, 2008, Arida, et al, 2009.…”
Section: Chronic Tlementioning
confidence: 91%